Critical Evaluation of Innovation Management in the Layanan Tanpa Lama (LANTALA) Program Within Digital Land Bureaucracy Reform - M.Nur Kamila Amrullah; Anang Pribadi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study is motivated by the persistently low level of public trust in land administration services in Indonesia, which are often perceived as slow, bureaucratic, and lacking service certainty. In response to these conditions, the Surakarta City Land Office introduced Layanan Tanpa Lama (LANTALA) as a digital-based fast-service innovation designed to accelerate land administration processes while supporting technology-based bureaucratic reform. This study aims to critically evaluate the implementation of LANTALA innovation management and analyze its contribution to improving the quality of public services in the land administration sector. This study employed a qualitative method with a case study design conducted at the Surakarta City Land Office involving 15 informants. Data were collected through in-depth interviews, participatory observation, and documentation, and were analyzed using thematic analysis through data reduction, coding, theme categorization, and interpretation of findings. The findings indicate that LANTALA has successfully improved service efficiency through workflow simplification, faster service delivery, and strengthened digital coordination among internal units. However, this study also identified several challenges, including digital infrastructure instability, increased employee workload, unequal service access, and low levels of public digital literacy. This study is limited to a single research location; therefore, future studies are recommended to adopt comparative cross-regional approaches to strengthen the generalizability of the findings